Self-Perceived Physical Attractiveness and Moral Intuitions as Mediators Between Somatic-Parental Effort and Mating Orientation - Andrzej Łukasik; Anna Wołpiuk-Ochocińska (Evolutionary Psychology)
Research suggests that physical attractiveness may be associated with more permissive moral norms, which can in turn lead to the adoption of a more liberal sexual strategy. However, different predictions arise from evolutionary Life History Theory and Moral Foundations Theory. We hypothesized that self-reported physical attractiveness and moral intuitions (innate morality) mediate the relationship between somatic-parental effort (SPE) and sociosexual desire - an indicator of mating orientation. The study involved 326 women aged 19-33 years. A sequential mediation analysis was conducted. As hypothesized, higher levels of SPE were associated with higher self-reported physical attractiveness. It was also shown that self-perceived physical attractiveness was a positive indicator of innate morality and that among all moral intuitions only Authority was a negative predictor of a preference for short-term relationships. Furthermore, in the studied women SPE was a direct positive predictor only of the intuition of Sanctity/Purity. However, the relationship between physical attractiveness in women following the slow reproductive strategy and sociosexual desire was characteristic of reproductive effort rather than somatic-parental effort. However, it was found that certain relationships between variables were in particular characteristic of women with a rural background. For this reason, the obtained results in the hypothesis context are significantly limited to this specific subpopulation of women.